Pengaruh Pengungkapan Islamic Social Reporting (ISR) Terhadap Kinerja Keuangan Pada Perbankan Syariah Di Indonesia Tahun 2012-2016 - Retnaningsih, Susi; Hariyanti, Widi; Astuti, Titiek Puji (IAIN Kudus, 2019)
This study aims to examine the influence of Islamic Social Reporting (ISR) disclosure on financial performance. The dependent variable used in this research is financial performance measured by Return on Asset (ROA) and Return on Equity (ROE). The independent variable in this research is The Islamic Social Reporting (ISR). This study uses firm size as a control variable. The population in this study is the sharia banking industry registered in the Financial Services Authority (OJK) period 2012-2016. The sample in this research is 10 Sharia banks chosen by using a purposive sampling method. This study uses a simple linear regression analysis as an analytical tool. The results showed that: (1) disclosure of Islamic Social Reporting (ISR) has a significant positive effect on Return on Assets (ROA). (2) disclosure of Islamic Social Reporting (ISR) has a significant positive effect on Return on Equity (ROE).